Behavioral Analysis of Sustained Individual Investors (European Journal of Marketing and Economics, 2025)
With a direct access to 32 self-directed investors from two European countries and the USA, we found that with experience, investors learn to mitigate well-studied behavioral biases while new biases and convictions emerge. The explorative interview method revealed reasons for seemingly irrational behavior not discovered by existing empirical studies using aggregated quantitative data. Thematic analyses were done using open coding and predefined concepts of mainstream and behavioral finance. The findings were contrasted with empirical literature and validated with expert interviews. Learning from mistakes, investors in our sample acknowledged the presence of emotions and built ways to mitigate behavioral issues. We found that overconfidence referenced in numerous studies diminishes after initial enthusiasm; underconfidence may emerge after painful losses. Illusion of control could not be identified. Instead, investors reported feeling of insufficient control on their investments. An important new bias candidate, tangibility bias was discovered which makes investors accept lower financial utility if they feel being in control of their investments. Tangibility bias contributes to less efficient portfolios due to the priority for small number of well-known investments instead of well-diversified but not transparent funds. Beyond decision-making biases, investors had developed experience-based convictions which may be rational or unfounded. Taking into account non-financial motivations, we argue that seemingly irrational actions have a purpose and efficacy.
Keywords: self-directed investing, behavioral biases, decision-making, ecological rationality, portfolio management, underconfidence